The Correlation Between Traditional Children's Songs (Lagu Dolanan) in Pre-Learning Activities and Socio-Emotional Development of Children Aged 5-6 Years - Afif Lailatus Sabila; Ahmad Ahmad Samawi; Munaisra Tri Tirtaningsih (Jurnal Caksana : Pendidikan Anak Usia Dini, 2026)
This study aims to analyze the correlation between the use of traditional children's songs (lagu dolanan) during pre-learning activities and the socio-emotional development of children aged 5–6 years at TK Taman Indria 1, Malang City, Indonesia. Socio-emotional development in early childhood is a critical foundation for future mental health, academic success, and social competence. However, many kindergartens have not optimally integrated traditional songs as a structured pedagogical tool. This research employed a quantitative correlational design involving 100 children selected through saturated sampling from groups A1, A2, B1, and B2. Data were collected using observation sheets, teacher questionnaires, and semi-structured interviews, all developed based on standardized socio-emotional indicators and song implementation metrics. The findings revealed that lagu dolanan use fell into the high category (mean = 49.57, SD = 1.289), with 89% of children demonstrating consistent engagement. Socio-emotional development scores were also high (mean = 64.32, SD = 2.093), with 92% of children showing age-appropriate emotional regulation and social skills. Because the data were not normally distributed (Shapiro-Wilk p < 0.05), a Spearman rank correlation test was conducted. The analysis yielded a correlation coefficient of rho = 0.489 (p = 0.000, p < 0.05), indicating a positive, significant relationship between the two variables. These results suggest that more structured and frequent implementation of traditional children's songs during pre-learning activities is associated with higher socio-emotional development. This study contributes original empirical evidence from an Indonesian early childhood context, filling a gap in quantitative studies on culturally grounded pedagogies. The findings support integrating local wisdom into daily teaching practices as an affordable, engaging, and effective strategy for holistic child development.